ANALISIS KESESUAIAN BUKU TEKS KIMIA KELAS XI SMA PADA MATERI SENYAWA HIDROKARBON DAN MINYAK BUMI - Nurhasnah, Merry (Journal of Technique Research (JTR), 2019)
Learning in the 2013 curriculum students are more required to be active in the learning process, in supporting student learning activities a media is needed that will help students in participating in school learning, one of them using a textbook. in this study aims to describe the quality of chemistry textbooks for class XI 2013 curriculum based on content suitability, and suitability presentation of material to be reviewed based on the university standard textbook by James E. Brady. Type of research that is used is qualitative research with descriptive methods. The results of the study showed that based on the conformity of the material in the 2013 curriculum chemistry textbook in accordance with the standard textbook used, not all of the hydrocarbon compounds in the standard textbook were explained in class XI. whereas in petroleum material there is no compatibility with the standard textbook used.